Growth performance, blood profiles and carcass traits of Barbary partridge (Alectoris barbara) fed two different insect larvae meals (Tenebrio molitor and Hermetia illucens) - Loponte, Rosa; Nizza, Sandra; Bovera, Fulvia; De Riu, Nicola; Fliegerova, Katerina; Lombardi, Pietro; Vassalotti, Giuseppe; Mastellone, Vincenzo; Nizza, Antonino; Moniello, Giuseppe (Research in veterinary science, 2017)
To investigate the effect of two insect meals (from Hermetia illucens, HI and Tenebrio molitor, TM larvae) on productive performance and blood profiles of Barbary partridge, ninety, seven days old partridges were divided into 5 groups (6 replicates, 3 partridges/replicate). Up to 64d, the groups fed 5 isoproteic and isoenergetic diets: the control fed a corn-soybean meal diet (SBM group); in TM25 and TM50 groups the 25 and 50% of SBM proteins were substituted by the protein from TM, respectively; in HI25 and HI50 groups the 25 and 50% of SBM were substituted by the protein from HI, respectively. The birds fed TM25 and both the HI levels reached a higher (P<0.01) live weight at 64d than the control. Considering the entire experimental period the TM groups had a more favorable FCR than SBM. The carcass weights of all the insect groups were higher (P<0.01) than the control. The weight of the full digestive tract in SBM group was the highest (P<0.01). The caecal weight, the intestinal and caecal length were the highest (P<0.01) in the SBM group. The SBM group the highest value of albumin/globulin (P<0.01) and creatinine (P<0.05). TM seems to be more effective than HI in improving FCR. The reduced albumin/globulin ratio in the insect meal fed groups could be ascribed to the chitin content and this result was not affected by the amount of chitin intake, suggesting that also the lowest values are able to express their potential effects in partridges.
Keywords: Tenebrio; Barbary partridge; Glycine max; Animal Feed; Diet; složení těla; larva; Growth performance; Carcass traits; Animal Nutritional Physiological Phenomena; Hermetia illucens; zvířata; Tenebrio molitor; křepelky a křepelovití; Galliformes; Blood profiles; krmivo pro zvířata; Diptera; dieta; fyziologie výživy zvířat; Body Composition; Larva; Animals; Quail